Simultaneous Equation Method for Simultaneous Estimation of Paracetamol and Ibuprofen in Combined Dosage Form. - Giri, Tapan (International Journal of Pharmaceutical & Biological Archive, 2010)
A simple reproducible simultaneous equation method, requiring no prior separation, has been developed for the estimation of ibuprofen and paracetamol in combined dosage form. Ibuprofen has absorbance maxima at 220 nm and paracetamol at 248.40 nm using ethanol as solvent. The method obeys Beer’s Law in concentration ranges employed for the estimation. The results of the analysis were validated statistically and recovery studies were carried out as per ICH guidelines. Also the developed method was successfully employed for dissolution studies in tablet dosage form.